Why are consistently-handed individuals more authoritarian? The role of need for cognitive closure. Issue 4 (3rd July 2020) - Lyle, Keith B.; Grillo, Michael C.
ABSTRACT: Recent studies indicate that individuals with consistent hand preference are more authoritarian than individuals whose preference is relatively inconsistent. We explored the role of epistemic needs in the handedness-authoritarianism relationship. Based on findings that consistent individuals are less cognitively flexible than inconsistent individuals, we hypothesized that consistent-handers would report greater need for definite knowledge. To measure this, we administered the revised Need for Cognitive Closure scale to a sample of undergraduates ( N = 235), along with measures of handedness consistency and authoritarian submission. Consistent individuals scored significantly higher on authoritarian submission and need for closure. Need for closure fully mediated the relationship between consistency and submission. Consistent individuals also expressed greater prejudice against authoritarian out-groups such as immigrants and liberals. This effect was partially mediated by authoritarian submission. We theorize that consistent-handers' cognitive inflexibility leads them to covet definite knowledge. These individuals turn to authoritarianism because it promises to stifle dissent and protect existing (conventional) knowledge.